The training of the educational psychologist for independent knowledge management as a professional requirement (Journal of Pharmaceutical Negative Results, 2022)
Currently, training the new generation of professionals is a challenge for universities, as presented in the Professional Model of the Bachelor's Degree in Education, Pedagogy-Psychology, which energize the formation of the labor resources that the country requires competently. Consequently, the mission of this career is to train workers suitable for a labor world in continuous change, which requires periodically recycling, reconverting or updating the professional competencies demanded by the economic and social development of the country related to pedagogical and psychological training. In this way, the article intends to support the need to train future educational psychologists in the independent management of knowledge based on a didactic model and the practical verification of the methodology that concretizes it in one of the disciplines of the career: Physiological and Psychological Foundations of Education (FFPE). Theoretical and empirical methods were used to carry out the research, particularly the experiential pedagogical experience, which revealed the methodology's effectiveness in transforming students towards higher stages in their professional protagonism.